2021
DOI: 10.3389/fneur.2021.608270
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Rescue Stenting and Antiplatelet Infusion Improved Outcomes for Acute Intracranial Atherosclerosis-Related Large-Vessel Occlusion

Abstract: Background and Purpose: Intracranial atherosclerosis-related large-vessel occlusion caused by in situ thrombo-occlusion (ICAS-LVO) has been regarded an important reason for refractoriness to mechanical thrombectomy (MT). To achieve better outcomes for ICAS-LVO, different endovascular strategies should be explored. We aimed to investigate an optimal endovascular strategy for ICAS-LVO.Methods: We retrospectively reviewed three prospective registries of acute stroke underwent endovascular treatment. Among them, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Despite the high incidence of ICAD-related intracranial arterial occlusions (especially in Asian populations in which they are the underlying cause for up to 40% of all large vessel occlusions) 3033 and that ICAD-related intracranial arterial occlusions might pose an independent risk factor for mechanical thrombectomy failure and early reocclusion, 34,35 no randomized-controlled clinical trial has evaluated the effects of hyperacute management approaches for these challenging situations. 36,37 The authors of these guidelines acknowledge that there is a need for well-designed randomized-controlled clinical trials to answer this clinically important question.…”
Section: Results: Pico Questionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the high incidence of ICAD-related intracranial arterial occlusions (especially in Asian populations in which they are the underlying cause for up to 40% of all large vessel occlusions) 3033 and that ICAD-related intracranial arterial occlusions might pose an independent risk factor for mechanical thrombectomy failure and early reocclusion, 34,35 no randomized-controlled clinical trial has evaluated the effects of hyperacute management approaches for these challenging situations. 36,37 The authors of these guidelines acknowledge that there is a need for well-designed randomized-controlled clinical trials to answer this clinically important question.…”
Section: Results: Pico Questionsmentioning
confidence: 99%
“…Our systematic review identified four retrospective studies of very low quality comparing the effects of angioplasty and/or stenting plus BMT after initial mechanical thrombectomy to BMT alone on functional outcome in ICAD-related intracranial arterial occlusions (see Table 3 for the GRADEpro ratings of the included studies). 37,[43][44][45] One out of the four studies compared LVO patients related to ICAD undergoing angioplasty and/or stenting to non-ICAD LVO patients with similar characteristics. 45 This study suggested that functional outcome did not differ between both groups, which would suggest that rescue therapy in the form of angioplasty and/or stenting appears to be safe.…”
Section: Picomentioning
confidence: 99%
See 2 more Smart Citations
“…However, preprocedural or earlier determination of an occlusion pathomechanism can be helpful for setting up an optimal endovascular strategy. As mechanical thrombectomy modalities are not so effective for an ICAS-related occlusion, rescue modalities, including glycoprotein IIb/IIIa inhibitors, percutaneous balloon angioplasty, and intracranial stenting, are frequently needed 23. Importantly, achieving a successful recanalization and elapsed time to recanalization are critical to patients' outcomes 7 24.…”
Section: Discussionmentioning
confidence: 99%